2017
DOI: 10.13040/ijpsr.0975-8232.8(6).2667-76
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background:Immunization is the most cost-effective intervention for infectious diseases which are the major cause of morbidity and mortality worldwide. There is a scarcity of information on the vaccination status of young adults and the role of socioeconomic conditions in India. Objectives: Present study explored the adult vaccination status and influence of income and education of parents on adult vaccination status in university students from Mumbai, India. Methods: On the basis of the eligibility criterion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
1
Order By: Relevance
“…A study conducted among undergraduate students found human papillomavirus (HPV) vaccine coverage to be 5.5% but we found it to be higher in this study (14.4%), probably because of the selection of doctors in our study who were likely to be more aware [ 5 ]. Recently, Sikkim became the first Indian state to introduce a free human papillomavirus vaccine in its routine immunisation programme for all girls between 9-14 years of age and achieved a high coverage of 97% [ 6 ].…”
Section: Discussioncontrasting
confidence: 61%
“…A study conducted among undergraduate students found human papillomavirus (HPV) vaccine coverage to be 5.5% but we found it to be higher in this study (14.4%), probably because of the selection of doctors in our study who were likely to be more aware [ 5 ]. Recently, Sikkim became the first Indian state to introduce a free human papillomavirus vaccine in its routine immunisation programme for all girls between 9-14 years of age and achieved a high coverage of 97% [ 6 ].…”
Section: Discussioncontrasting
confidence: 61%